P-070 Comparison of Microfluidic Sperm Sorting (MFSS) versus Physiological Intracytoplasmic Sperm Injection (PICSI) versus Density Gradient versus Swim Up in high DNA fragmentation index sperm samples. (30th June 2022) - Nayar, K.D; Gupta, S; Sanan, S; Aggarwal, S; Kant, G; Nayar, K; Sharma, H
Abstract: Study question: To evaluate the effectiveness of using Microfluidic Sperm Sorting (MFSS) over other technique in patient with high DNA fragmentation index (DFI) sperm samples? Summary answer: Microfluidic is not only correlated with better DNA integrity but also with the better reproductive outcome. What is known already: DNA damage is unrecognisable in living sperm prior to insemination and an increased sperm DNA fragmentation index has been associated with lower fertilization rates, impaired embryo development and reduced pregnancy rates. Standard semen processing techniques are associated with centrifugation, which may induce reactive oxygen species and DNA damage. In strategies to minimize sperm DNA fragmentation, Physiological ICSI can relatively reduce sperm DNA fragmentation by 67.9% (Parmegiani et al., 2010) while new technique Microfluidic sperm sorter technique also demonstrate sperm selection with significantly reduced DNA damage Study design, size, duration: A prospective randomised study was conducted from 1st January 2019 to 1st December 2021. Four hundred patients were randomised by computer generated list and divided into 4 groups. Group A (n = 100), in which sperm were processed by microfluidic sperm sorter (MFSS) while in group B (n = 100), sperm were selected by Physiological Intracytoplasmic Sperm Injection (PICSI), Group C (n = 100), sperm were processed by density gradient and Group D (n = 100), sperm were processed by swim-up technique. Participants/materials, setting, methods: The study period included all normozoospermic patients with high DNA fragmentation index (>25%) while oligospermic, asthenozoospermic samples, patients with poor ovarian reserve and advanced age were excluded from the study. All A grade embryos were vitrified and transferred in frozen embryo replacement cycle. All the 3 groups were compared on the basis of fertilisation rate, day 3 grade A embryo development rate, clinical pregnancy rate and miscarriage rate. Main results and the role of chance: Cycle characteristics (female age, length of stimulation, gonadotrophin dose, number of oocytes and number of transferred embryos) were similar among all 4 groups. Among 4 groups, There was a statistically significant increase observed in Group A (Microfluidic Sperm Sorting), day 3 grade A embryo development rate (60% vs. 42% vs. 38% vs. 40%, p-0.016) and clinical pregnancy rate (62% vs. 46% vs. 41% vs 43%, p-0.049), while no statistical significant difference observed in fertilisation rate (82% vs. 78% vs. 76% vs. 78%, p-0.80) comparing group B, group C and group D. But significantly higher miscarriage rate (12% vs. 11% vs. 25%, 12%) observed in density gradient (Group C) technique. Limitations, reasons for caution: Larger randomised control studies are needed to strengthen these results. Wider implications of the findings: We have demonstrated that sperm sorted by microfluidic helps in selection of sperm with better DNA integrity over Physiological ICSI, Density Gradient and Swim-up techniues. Using it in routine practice can help in reducing the negative effect of reactive oxygen species and thus improve pregnancy rate and live birth rate. Trial registration number: MCDH/2019/35